Current Advances in Information Quantum Technologies – Critical Issues - Nałęcz-Charkiewicz, Katarzyna; Meles, Jana; Rzęsa, Wioleta; Wojciechowski, Andrzej A.; Warchulski, Eryk; Kania, Kacper; Stypułkowska, Justyna; Fluder, Grzegorz; Romaniuk, Ryszard S. (International Journal of Electronics and Telecommunications, 2021)
This article reviews chosen topics related to the development of Information Quantum Technologies in the major areas of measurements, communications, and computing. These fields start to build their ecosystems which in the future will probably coalesce into a homogeneous quantum information layer consisting of such interconnected components as quantum internet, full size quantum computers with efficient error corrections and ultrasensitive quantum metrology nodes stationary and mobile. Today, however, the skepticism expressing many doubts about the realizability of this optimistic view fights with a cheap optimism pouring out of some popular press releases. Where is the truth? Financing of the IQT by key players in research, development and markets substantially strengthens the optimistic side. Keeping the bright side with some reservations, we concentrate on showing the FAST pace of IQT developments in such areas as biological sciences, quantum evolutionary computations, quantum internet and some of its components.
Keywords: information quantum technologies; quantum sensorsand timing; quantum computing applications; quantum genetic algorithms; quantum communications and internet